Hematological parameters of Pimelodus maculates (Osteichthyes: Pimelodidae) from polluted and non-polluted sites in the Itajaí-Açu river, Santa Catarina State, Brazil - DOI: 10.4025/actascibiolsci.v31i2.3267 (Acta Scientiarum. Biological Sciences, 2009)
This study evaluated the hematological response of Pimelodus maculates captured in two environments with different levels of pollution in the Itajaí-Açu river, Santa Catarina State, southern Brazil. One of them, hereby named reference site, is a water captation site that supplies the city of Blumenau, in which the riparian forest is preserved and there is no sewage discharge. The other, denominated polluted site, is characterized by discharge of domestic sewage. After water quality analysis, fish were captured, transported to the laboratory and anesthetized for the hematological exam. In the polluted site, the most probable number of fecal coliforms and water transparency were respectively higher and lower than that observed at the reference site. The main results were an increased percentage of hematocrit and reduced numbers of lymphocytes and monocytes in the differential counting in fish from the polluted site. Red blood cells, total white blood cells and total counting of thrombocytes did not vary between environments. The number of neutrophils remained at high levels in fish from both environments. This study demonstrated that water quality might affect the hematological parameters in free-living fish.